Professional Competence of Islamic Religious Education Teachers in Using E-Learning-Based Learning Media at Mts Arafah Binjai - Nafisah, Adinda Kamilah; Salim, Agus (Lembaga Riset Mutiara Akbar, 2025)
The development of information technology has brought relevant changes in the world of education. This reserch aiming to identify and analyze the professional competence of Islamic Religious Education teachers in the use of e-learning-based learning media at Mts Arafah Binjai. The approach used by the author in this study is qualitative, namely to understand the phenomenon of what is experienced by the research subjects. Based on the results of the study conducted at Mts Arafah Binjai, it can be concluded that the professional competence of Islamic Religious Education teachers in the use of e-learning-based learning media is still not optimal. In addition, the results of this study can be a reference for educational institutions to design training programs and procure more adequate e-learning facilities and infrastructure, in order to support the transformation of technology-based education in the madrasah environment.